Implementasi Undang-Undang Perlindungan Konsumen Dalam Transaksi Elektronik - Rahma Yulia; Riri Rardayani; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2025)
There is a new feature in the trading system due to the rapid advancement of information technology. After several years, transactions are increasingly being carried out in Indonesia using online media. Sometimes, online sales transactions use social media platforms such as Facebook or mobile phones as a means of communication. This internet-based business model also applies to virtual systems, stores and virtual companies where business actors run their businesses and trade through the internet and no longer rely on real conventional company businesses. The formulation of the problem is 1) Implementation of Law Number 8 of 1999 concerning consumer protection in electronic transactions in Indonesia, 2) The role of the government in supervising and enforcing consumer protection in digital transactions of the Consumer Protection Agency in Indonesia. To answer these problems, a type of normative juridical research is used, namely a method of data collection that involves understanding and studying theories from various literature sources that are relevant to the research. 1. Consumer protection is an important part of the legal system that strengthens the bond between consumers and business owners, in order to protect consumer rights in the consumption of goods and services. Regulation Number 8 of 1999 concerning Consumer Protection (UUPK) is the main legal basis 2. Consumer Protection Institutions in Indonesia have an important role in protecting consumer rights from injustice in transactions of goods and services. One of the main organizations is the Consumer Dispute Resolution Agency (BPSK), which was established as an alternative to the official courts for the courts.